ANALISIS YURIDIS TERHADAP BELUM DIRATIFIKASINYA KONVENSI 1951 TENTANG STATUS PENGUNGSI OLEH INDONESIA - Natasya Fahira (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2021)
Abstract As one of the countries that has not ratified the 1951 Convention Relating to the Status of Refugees and its 1967 Protocol, Indonesia does not yet have a special system and policy for dealing with refugees. The existence of refugees in Indonesia is generally long-term before refugees are then placed back in a third country (resettlement). The lack of regulations pertaining to what refugees can do while residing in Indonesia clearly narrows the space for refugees to move. The limited space for movement makes it difficult for refugees to access their needs, especially in the aspects of livelihood, health, and education. For this reason, this paper can be seen as a first step to examine the reasons why the 1951 Convention has not been ratified by Indonesia, as an effort to handle and protect refugees from abroad. This research is conducted using normative-juridical method. Keywords: refugee, 1951 convention, ratification, Indonesia. ______________________________________________________________________ Abstrak Sebagai salah satu negara yang tidak meratifikasi Konvensi 1951 tentang Status Pengungsi beserta Protokol 1967, Indonesia belum memiliki sistem dan kebijakan khusus untuk menangani pengungsi. Keberadaan pengungsi di Indonesia pada umumnya bersifat jangka panjang, sebelum kemudian pengungsi ditempatkan kembali ke negara ketiga (resettlement). Minimnya peraturan mengenai hal-hal apa saja yang dapat dilakukan oleh pengungsi selama berada di Indonesia jelas mempersempit ruang gerak pengungsi. Keterbatasan ruang gerak tersebut mengakibatkan pengungsi kesulitan untuk mengakses kebutuhan-kebutuhannya, terutama dalam aspek penghidupan, kesehatan, dan pendidikan. Untuk itu, tulisan ini dapat dipandang sebagai langkah awal untuk mengkaji alasan belum diratifikasinya Konvensi 1951 oleh Indonesia, sebagai upaya penanganan dan perlindungan pengungsi dari luar negeri. Kata kunci: pengungsi, konvensi 1951, ratifikasi, Indonesia.